Broad‐Spectral‐Range Sustainability and Controllable Excitation of Hyperbolic Phonon Polaritons in α‐MoO3. Issue 46 (27th September 2020) - Dong, Weikang; Qi, Ruishi; Liu, Tiansheng; Li, Yi; Li, Ning; Hua, Ze; Gao, Zirui; Zhang, Shuyuan; Liu, Kaihui; Guo, Jiandong; Gao, Peng
Abstract: Hyperbolic phonon polaritons (HPhPs) in orthorhombic‐phase molybdenum trioxide (α‐MoO3 ) show in‐plane hyperbolicity, great wavelength compression, and ultralong lifetime, therefore holding great potential in nanophotonic applications. However, its polaritonic response in the far‐infrared (FIR) range remains unexplored due to challenges in experimental characterization. Here, monochromated electron energy loss spectroscopy (EELS) in a scanning transmission electron microscope (STEM) is used to probe HPhPs in α‐MoO3 in both mid‐infrared (MIR) and FIR frequencies and correlate their behaviors with microstructures and orientations. It is found that low structural symmetry leads to various phonon modes and multiple Reststrahlen bands (RBs) over a broad spectral range (over 70 meV) and in different directions (55–63 meV and 119–125 meV along the b ‐axis, 68–106 meV along the c ‐axis, and 101–121 meV along the a ‐axis). These HPhPs can be selectively excited by controlling the direction of swift electrons. These findings provide new opportunities in nanophotonic and optoelectronic applications, such as directed light propagation, hyperlenses, and heat transfer. Abstract : Hyperbolic phonon polaritons in α‐MoO3 are measured in a broad spectral range using electron energy loss spectroscopy. Polaritons with different dispersion types can be sustained in multiple Reststrahlen bands covering both mid‐ and far‐infrared frequencies, and can be selectively excited by the electron beam. These findings provide new opportunities in nanophotonic applications such as directed light propagation and hyperlensing.